Field Guide for Portland Cement Concrete Construction in Antarctica. - Keeton, John R. (1969)
The technical note was prepared for field use by military crews in producing, placing and curing Portland cement concrete in Antarctica under summer temperatures down to 15F. Since the principal factors are mix control and mix temperature during production and exposed surface temperature control for 3 days following placement, these steps are discussed in considerable detail. The technical information presented in this document is based on field experiments at McMurdo Station, Antarctica, during Deep Freeze 69, which are described in Naval Civil Engineering Laboratory Technical Report 'Portland Cement Concrete for Antarctica.' (Author)